Chemistry of Diabetes and its Impact - Mishra, Birendra Kumar (Academic Voices: A Multidisciplinary Journal, 2013)
Diabetes mellitus is caused by defects in insulin production as will as action. In absence of insulin ,the body’s primary source of energy and the brains only source of energy, glucose is unable to enter into cells. Infact diabetes mellitus is a metabolic disease i.e. it is caused by an abnormal metabolism resulting from, for example nutritional deficiency, enzyme deficiency or abnormal secretion of hormones. In a case study among Nepalese people it has been found that diabetes mellitus is mainly caused by deterioration of renal function (Chronic Kidney Disease) . Obesity and type 2 diabetes relation is an active and exciting area of research now a days . In this article an attempt has been made to overview the life threatening disease diabetes mellitus. Academic Voices, Vol. 2, No. 1, 2012, Pages 16-22 DOI: http://dx.doi.org/10.3126/av.v2i1.8279